Baron Eduard von Toll's Last Expedition: The Russian Polar Expedition, 1900-1903 - Barr, William (ARCTIC, 1981)
Zarya, the expedition vessel of the Russian Polar Expedition of 1900-1903 mounted by the Imperial Academy of Sciences and led by arctic geologist Baron Eduard von Toll, sailed from St. Petersburg on 21 June 1900. Toll planned to spend a first winter on the little-known east coast of Poluostrov Taymyr, and a second winter on "Zemlya Sannikova", a landmass which he believed lay to the north of the Novosibirskiye Ostrova. Owing to ice conditions, Zarya spent her first winter on the west coast of Poluostrov Taymyr, where the expedition members made substantial contributions to knowledge of the geography, meteorology, geology, biology and magnetology of the area. A search for "Zemlya Sannikova" during the 1901 navigation season proved inconclusive and Zarya spent the second winter of the expedition at Bukhta Nerpalakh on Ostrov Kotel'nyy. In spring of 1902 Toll with three companions started north for Ostrov Bennetta by sledge and kayak. Zarya attempted to reach Ostrov Bennetta to evacuate the baron's party but was unable to do so because of severe ice conditions. Two search parties were dispatched in the spring of 1903; one, under M.I. Brusnev, searched the shores of the Novosibirskiye Ostrova; the other, led by A.V. Kolchak, travelled by whaleboat to Ostrov Bennetta. There he found signs that the Baron and his companions had reached the island, and also a note to the effect that they had left the island again, by kayak, in November 1902. No further traces of the four men have ever been found.